THE BIOLOGICAL FUNCTIONS OF IMMUNOGLOBULIN Y (IgY) MOLECULES IN AGAINST INFECTION OF Enterococcus faecalis ORIGIN OF RED TILAPIA - Rifky Rizkiantino; Fachriyan Hasmi Pasaribu; Retno Damajanti Soejoedono; Wyanda Arnafia; Dinda Reisinta; I Wayan Teguh Wibawan (Jurnal Kedokteran Hewan, 2022)
Red tilapia (Oreochromis hybrid) is Indonesia's leading freshwater fishery commodity susceptible to streptococcal bacterial infection. Many studies have been conducted on various efforts to prevent and treat this disease, one of which uses the immunoglobulin Y (IgY) molecule from chicken egg yolk. This study aimed to observe the biological function of IgY against Enterococcus faecalis as a cause of streptococcal-like infection. The agglutinin function was conducted by observing the growth of Enterococcus faecalis in brain heart infusion (BHI) broth media which was added with IgY suspension. The function of inhibin was performed using a spectrophotometric method to measure the level of turbidity of the bacterial suspension inoculated with IgY suspension. The bactericidal potential through the complementary activation pathway for red tilapia serum was carried out using a scanning electron microscope (SEM) method to evaluate the topography of the bacterial cell wall. The results of the study can be concluded that IgY anti-Enterococcus faecalis has the potential as an agglutinin, inhibin, and bactericidal agent through its putative potential in complement activation in streptococcal bacterial infections in red tilapia commodities.